Use of Metaphors and Metonymy in Economic Discourse - Sazdovska Pigulovska, Milena (University “St. Kliment Ohridski” – Bitola, 2017)
Considering the great interest in economics as a science due to the dynamic developments in the international business environment, growing attention is dedicated to the specific use and manner of organisation of language in a specific professional context. Subject of research in this paper is the economic discourse, in particular the use of metaphors and metonymy as mechanisms for conveying ideas and designating economic terms. The economic discourse is a type of professional discourse or specialised use of language in a specific (academic and professional) environment, whereas, at the lexical level, there is a possibility for metaphorical and metonymical expression when naming specialised economic terms. Hence, the purpose of this paper is to adequately define the types of economic metaphors on the grounds of a corpus-based analysis, as well as to analyse their function in the text. Furthermore, examples of metonymy will also be analysed.
Keywords: Economic metaphors, metonymy, economic discourse, specialised terminology